Diferencial de salários público-privado e ciclo econômico no Brasil - Martins, Fernando Fabian De Freitas [UNIFESP] (2021)
This paper analyzes the wage premium paid to the Brazilian state government employees compared to the private sector ones. This differential is estimated with Mincerian equations using 1995 to 2015 annual data from the National Household Sample Survey (PNAD/IBGE) and corrected for selection bias by a bivariate probit model for the probabilities of taking part in the labor force and being a public employee. Once the public-private wage differentials are obtained for each year and state government, they are adopted as the dependent variable in a panel data approach to verify the hypothesis of a countercyclical behavior. The covariates used are the unemployment rate, public finance indicators, the percentage of public employees over total employment, industry share in GDP, and variables to identify electoral cycles. For the panel data models, we used different estimation methods and tested for the hypothesis of heterogeneity of impacts of the labor market and public finance covariates across states. Our findings show that the wage differential has a countercyclical behavior tied to a more rigid labor market in the public sector. However, the relation between the pay gap and the unemployment rate was found to be nonlinear, and for high levels of unemployment, the earnings of public employees are also affected.